Structure determination techniques flex their muscles - Blake, Alexander J. (Wiley-VCH Verlag, 2017)
A historical challenge: Gas-phase electron diffraction and single-crystal X-ray diffraction are both established techniques, but they were both pushed to their limits by the challenge posed by the highly flexible tetranitromethane molecule. New approaches had to be developed for the structure of the molecule to be elucidated.